Australianama : the South Asian odyssey in Australia - Khatun, Samia (London : Hurst Publishers, 2018)
The first major history of South Asian migration to Australia. Australian deserts remain dotted with the ruins of old mosques. Beginning with a Bengali poetry collection discovered in a nineteenth-century mosque in the town of Broken Hill, Samia Khatun weaves together the stories of various peoples colonised by the British Empire to chart a history of South Asian diaspora. Australianama (The Book of Australia) composes a history of Muslims in Australia through Sufi poetry, Urdu travel tales, Persian dream texts and Arabic concepts, as well as Wangkangurru song-poetry, Arabunna women's stories and Kuyani histories, leading readers through the rich worlds of non-white peoples that are missing from historical records. Khatun challenges a central idea that powerfully shapes history books across the Anglophone world: that European knowledge traditions are superior to the epistemologies of the colonised. Arguing that Aboriginal and South Asian language sources are keys to the vast, complex libraries that belie colonised geographies, Australianama shows that stories in colonised tongues can transform the very ground from which we view past, present and future.
Includes bibliographical references (pages 235-255) and index.
ENH
Keywords: East Indians -- Australia -- History; Acculturation -- Australia -- History; Australia -- History